2011
DOI: 10.1128/jb.01252-10
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Evidence for l -Fucose Utilization by Campylobacter jejuni

Abstract: Campylobacter jejuni remains among the leading causes of bacterial food-borne illness. The current understanding of Campylobacter physiology suggests that it is asaccharolytic and is unable to catabolize exogenous carbohydrates. Contrary to this paradigm, we provide evidence for L-fucose utilization by C. jejuni. The fucose phenotype, shown in chemically defined medium, is strain specific and linked to an 11-open reading frame (ORF) plasticity region of the bacterial chromosome. By constructing a mutation in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 53 publications
7
120
0
Order By: Relevance
“…For instance, C. jejuni tolerates well an elevated growth temperature of 42°C, which is the body temperature of many avian species, and has developed a microaerobic metabolism likely reflecting the low oxygen tensions present in the chick gut (43). Other than a fucose uptake and utilization system present in some C. jejuni strains, many C. jejuni strains appear to rely on amino acids rather than sugars as carbon sources (11,32,39,41). Investigations have found that serine, aspartic acid, glutamic acid, and proline are depleted from media during in vitro growth of C. jejuni (11,25,31,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, C. jejuni tolerates well an elevated growth temperature of 42°C, which is the body temperature of many avian species, and has developed a microaerobic metabolism likely reflecting the low oxygen tensions present in the chick gut (43). Other than a fucose uptake and utilization system present in some C. jejuni strains, many C. jejuni strains appear to rely on amino acids rather than sugars as carbon sources (11,32,39,41). Investigations have found that serine, aspartic acid, glutamic acid, and proline are depleted from media during in vitro growth of C. jejuni (11,25,31,44).…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, LivJ has been shown to be involved in the transport of alanine, serine, and threonine, albeit at reduced levels compared to branched-chain amino acids (38). The metabolism of many C. jejuni strains is largely dependent on amino acids rather than sugars as carbon sources (17,25,27,31,32,41,44). In metabolic studies, C. jejuni was shown to primarily utilize serine, aspartic acid, asparagine, glutamic acid, and, to a lesser extent, glutamine, threonine, and proline when grown in complex medium, CDMϩ, or minimal medium with single amino acids exogenously supplied (11,17,25,44).…”
mentioning
confidence: 99%
“…In addition to mucin, organic acid intermediates of the TCA cycle as well as some amino acids, L-fucose was identified as a chemoattractant for Campylobacter jejuni (Hugdahl et al, 1988). Campylobacter jejuni binds to 1,2-a-fucosylated glycans in vitro and adherence to intestinal cells is diminished by free fucose (Muraoka & Zhang, 2011). Similar to Bacteroides thetaiotaomicron, the anaerobic utilization of fucose by Campylobacter jejuni results in pyruvate production (Stahl et al, 2012).…”
Section: L-rhamnose and L-fucose Utilization By Enteric Pathogensmentioning
confidence: 99%
“…Additionally, they can be frequently found in plant cell wall polysaccharides and in bacterial exopolysaccharides (Sampson & Bobik, 2008). a-Linked L-fucose represents 4-14 % of the total oligosaccharide content of mucin and is one of the terminal sugars of the oligosaccharide chains attached to the protein backbone of mucins (Muraoka & Zhang, 2011). Both sugars are derived from ingested food or from shedding and turnover of epithelial cells, and at least fucose is abundant in the intestine (Robbe et al, 2004).…”
Section: Mucus-derived Nutrients and The Proliferation Of Commensal Amentioning
confidence: 99%
“…Briefly, the ribosomal DNA sequence was amplified and cloned into the pGEM-T Easy plasmid (Promega), which was subsequently digested with MfeI. The chloramphenicol acetyltransferase gene was amplified from pUOA18 (47) and inserted into the digested plasmid to produce pRRC (35). The luxS gene, along with 500 bp of its upstream sequence containing the putative promoter region, was cloned into an XbaI site of pRRC located upstream of the chloramphenicol resistance determinant.…”
Section: Methodsmentioning
confidence: 99%